Implementation of a chatbot for virtual attention of queries Case: Postgraduate School of the UNMSM (LACCEI, 2024)
The COVID-19, in different businesses, has generated the need to migrate from face-to-face attention to virtual attention, for the DGEP (Dirección General de Estudios de Posgrado de la Universidad Nacional Mayor de San Marcos) face-to-face attention to those interested in making consultations regarding postgraduate studies was simply impossible considering that, due to the sanitary measures taken during the pandemic, the university closed its doors. The alternatives to continue attending could have been the implementation of the telephone consultation service or text messages, however, these alternatives had drawbacks such as: a high percentage of unattended queries, the fact that many users wished to make queries after regular working hours, the existence of frequent queries and the delay in responses therefore, in the present research a chatbot has been implemented to ensure the virtual attention of queries from the public providing an online attention, with adequate answers and 24 hours a day. Optimally satisfying the doubts of students and those interested in postgraduate studies allows reaching a greater number of applicants to the various specialties offered by the DGEP. As a result, 100% of the queries have been attended in a timely manner, reducing the average time of attention per use.